The Characteristics of Spike Glycoprotein Gene of Swine Acute Diarrhea Syndrome Coronavirus Strain CH/FJWT/2018 Isolated in China - Guo, Yan-Yan; Wang, Pei-Hua; Pan, Yuan-Qing; Shi, Rui-Zhu; Li, Ya-Qian; Guo, Fan; Xing, Li (Frontiers in Veterinary Science, 2021)
Swine acute diarrhea syndrome (SADS) is a highly contagious infectious disease characterized by acute vomiting and watery diarrhea in neonatal piglets. The causative agent for SADS is the swine acute diarrhea syndrome coronavirus (SADS-CoV), an alphacoronavirus in the family Coronaviridae. Currently, SADS-CoV was identified only in Guangdong and Fujian provinces of China, not in any other regions or countries in the world. To explore the genetic diversity of SADS-CoV isolates, herein we comparatively analyzed 44 full-length genomes of viruses isolated in Guangdong and Fujian provinces during 2017-2019. The spike glycoprotein gene of SADS-CoV strain CH/FJWT/2018 isolated in Fujian province is distinct from that of other viral isolates in either spike glycoprotein gene-based phylogenetic analysis or whole genome-based gene similarity analysis. Moreover, at least 7 predicted linear B cell epitopes in the spike glycoprotein of CH/FJWT/2018 would be affected by amino acid variations when compared with a representative virus isolated in Guangdong province. The spike glycoprotein of coronaviruses determines viral host range and tissue tropism during virus infection via specific interactions with the cellular receptor and also plays critical roles in eliciting the production of neutralizing antibodies. Since SADS-CoVs have a broad cell tropism, the results in this report further emphasize that the spike glycoprotein gene is a pivotal target in the surveillance of SADS-CoV.